The coupled effect of climate change and LUCC on meteorological drought in a karst drainage basin, Southwest China - Zhonghua He; Xiaolin Gu; Maoqiang Wang; Mingjin Xu (Scientific Reports)
Abstract With global warming and the acceleration of the water cycle, the frequency and severity of droughts have progressively increased. Although Southwest China is located inland, the combined effects of global climate change, regional climate anomalies, and human activities have led to a diversified set of driving mechanisms for meteorological droughts. Based on monthly global and regional meteorological factors (10 global factors and 8 regional factors) and land use/land cover data from 1948 to 2023, this study employs classical correlation analysis, wavelet analysis, and Bayesian principles to explore the temporal and spatial evolution characteristics of meteorological droughts in Southwest China, as well as their driving mechanisms. The results show that: (1) between 1948 and 2023, meteorological droughts in Southwest China exhibited a north-south (annual average, spring, and winter) or east-west decreasing trend (autumn) and alternating east-west intensity in summer. The drought frequency ranged from 0.35 to 0.39, generally showing a decreasing trend from southwest to northeast. (2) Global atmospheric circulation significantly influences meteorological droughts in Southwest China, especially during El Niño years, when global atmospheric circulation factors such as Nino 3.4 and SOI have a more prominent impact on drought, particularly in the summer and autumn. In contrast, during La Niña years, drought intensity and frequency are more pronounced in spring and autumn. Regional climate factors, particularly temperature and evapotranspiration, also have a significant effect on drought across different seasons, especially in winter and spring, when higher temperatures and evapotranspiration exacerbate droughts, and precipitation has a relatively weaker effect. (3) Land use changes significantly affect meteorological droughts in Southwest China, with a driving probability ranging from 0.39 to 0.42. Under different climate conditions, the driving probabilities of land use changes are ranked as follows: El Niño years (0.32–0.52) > Normal years (0.31–0.51) > La Niña years (0.27–0.50). In particular, land use changes such as the expansion of built-up areas and the reduction of farmland could intensify the frequency and severity of meteorological droughts in drought-prone areas. Additionally, the reduction of green spaces or forests may also exacerbate droughts, especially during the urbanization process. Notably, during El Niño years, the driving effect of various landforms on drought shows different skewed distributions. Therefore, this study clarifies, to some extent, the evolution and mechanisms of meteorological droughts in Southwest China and provides technical guidance and theoretical support for drought prevention and disaster relief efforts in the Karst region.